Internet Corporation for Assigned Names and Numbers: An Overview - Paul, P. K.; Bhuimali, A.; Shivraj, K.S (Asian Journal of Engineering and Applied Technology, 2016)
Internet is a global system which is basically interconnected computer networks and spread around the world. The network of networks, internet basically composed and consists with millions of several kind of private, public, academic, business and commerce, administrative and government, health and medical computer systems. Today millions of people are using internet but it is a fact that there is no control or property or authority on this system; however the internet name space and also Domain Name System basically governed by the ICANN and the technical standard and similar activities hundred by the IETF (i.e.) Internet Engineering Task Force. The ICANN was established on 1998 in California, USA. This paper is an overview based literature on ICANN; including its activities, functions, structure, and other similar activities.